Amino acids as possible alternative nitrogen source for growth of Euglena gracilis Z in life support systems - Richter, Peter; Liu, Y.; An, Y.; Li, X.; Nasir, Adeel; Strauch, Sebastian; Becker, Ina; Krüger, Julia; Schuster, Martin; Ntefidou, Maria; Daiker, Viktor; Haag, Ferdinand; et al. (Life Sciences in Space Research, 2015)
In recent times Euglena gracilis Z was employed as primary producer in closed environmental life-support system (CELSS), e.g. in space research. The photosynthetic unicellular flagellate is not capable of utilizing nitrate, nitrite, and urea as nitrogen source. Therefore, ammonium is supplied as an N-source in the lab (provided as diammonium-dihydrogenphosphate, (NH)HPO) to E. gracilis cultures. While nitrate exerts low toxicity to organisms, ammonium is harmful for many aquatic organisms especially, at high pH-values, which causes the ionic NH4+ (low toxicity) to be partially transformed into the highly toxic ammonia, NH. In earlier reports, Euglena gracilis was described to grow with various amino acids as sole N-source. Our aim was to investigate alternatives for (NH)HPO as N-source with lower toxicity for organisms co-cultivated with Euglena in a CELSS. The growth kinetics of Euglena gracilis cultures was determined in the presence of different amino acids (glycine, glutamine, glutamic acid, leucine, and threonine). In addition, uptake of those amino acids by the cells was measured. Cell growth in the presence of glycine and glutamine was quite comparable to the growth in (NH)HPO containing cultures while a delay in growth was observed in the presence of leucine and threonine. Unlike, aforementioned amino acids glutamate consumption was very poor. Cell density and glutamate concentration were almost unaltered throughout the experiment and the culture reached the stationary phase within 8 days. The data are compared with earlier studies in which utilization of amino acids in Euglena gracilis was investigated. All tested amino acids (glutamate with limitations) were found to have the potential of being an alternative N-source for Euglena gracilis. Hence, these amino acids can be used as a non-toxic surrogate for (NH)HPO.
Keywords: Amino-acids; CELSS; Euglena gracilis; Nitrogen source

Delayed fluorescence, steady state fluorescence, photosystem II quantum yield as endpoints for toxicity evaluation of Cu2+ and Ag+ - Strauch, Sebastian; Richter, Peter; Haag, Ferdinand; Krüger, Marcus; Krüger, Julia; Azizullah, Azizullah; Breiter, Roman; Lebert, Michael (Environmental and Experimental Botany, 2016)
The effect of copper and silver ions on photosynthetic parameters of the flagellate Euglena gracilis was determined. The photosystem II quantum yield (Y) and steady state fluorescence (F) were measured with a PAM-fluorometer, while delayed fluorescence (DF) was determined by means of a sensitive single-photon camera attached to an image analysis device, which counted the relative number of photons released from the algae in darkness after previous light-stimulation. We found that after 3 h of incubation photosynthesis was affected only in the presence of relatively high concentrations of the used noble metals. The obtained EC values for Cu were 505.8 mg L (Y ), 286.5 mg L (DF), and 491.0 mg L (F). The EC values for silver ions were 51.9 mg L (Y ), 51.8 mg L (DF) (values for F not determinable). Photosynthesis is far less sensitive against toxic noble metals compared to motility parameters as reported in earlier studies, in part because the organelles of photosynthesis, the chloroplasts, are well protected from external substances within the cell, while flagella, reaching into the surrounding of the cell, are more easily influenced. As chloroplasts are easily accessible by means of non-invasive methods e.g. PAM- fluorometry, they are probably interesting model systems in order to detect effects of substances deep inside the cell. Influence on the chloroplasts is a measure that a germicide entered the cells, diffused through the cytoplasm and the membranous systems and reached compartmentalized enzyme complexes.
Keywords: Delayed fluorescence; Ecotoxicology; Euglena gracilis; PAM-fluorometry; Photosynthetic yield; Steady state fluorescence

Eu:CROPIS - "Euglena gracilis: Combined Regenerative Organic-food Production in Space" - A Space Experiment Testing Biological Life Support Systems Under Lunar And Martian Gravity - Hauslage, Jens; Strauch, Sebastian; Essmann, Olaf; Haag, Ferdinand; Richter, Peter; Krüger, Julia; Stoltze, Julia; Becker, Ina; Nasir, Adeel; Bornemann, Gerhild; Mueller, Hartmut; Delovski, Toni; et al. (Microgravity Science and Technology, 2018)
Human space exploration needs stable life support systems for the supply of oxygen, water and food for each human explorer due to long term missions. The most promising approach for building stable life support systems is a combination of physico-chemical and biological systems. These hybrid systems combine the reliability of physico-chemical and the sustainability of biological life support systems. Also the disadvantages, which are the finite resources of physico-chemical and the imperfect reliability of biological systems, are mutually balanced. To improve the reliability of biological life support systems, a combination of different biological systems may stabilize the whole approach during long term operations. The satellite mission Eu:CROPIS (Euglena gracilis: Combined Regenerative Organic-food Production In Space) is a testbed for investigating the behavior of combined biological life support systems under the influence of altered gravity, here, Lunar and Martian gravity. The core systems are a biological trickle filter for processing urine into a fertilizer solution via nitrification and Euglena gracilis, a photosynthetic protist which is able to produce oxygen and biomass while protecting the whole system against high ammonia concentrations.
Keywords: Compact satellite; Life support system; Moon; Mars; Reduced gravity; Nitrification

How the space environment influences organisms: An astrobiological perspective and review - Prasad, Binod; Richter, Peter; Vadakedath, Nithya; Haag, Ferdinand; Strauch, Sebastian M.; Mancinelli, Rocco; Schwarzwälder, Achim; Etcheparre, Emmanuel; Gaume, Nicolas; Lebert, Michael (International Journal of Astrobiology, 2021)
The unique environment of space is characterized by several stress factors, including intense radiation, microgravity, high vacuum and extreme temperatures, among others. These stress conditions individually or in-combination influence genetics and gene regulation and bring potential evolutionary changes in organisms that would not occur under the Earth's gravity regime (1 × g). Thus, space can be explored to support the emergence of new varieties of microbes and plants, that when selected for, can exhibit increased growth and yield, improved resistance to pathogens, enhanced tolerance to drought, low nutrient and disease, produce new metabolites and others. These properties may be more difficult to achieve using other approaches under 1 × g. This review provides an overview of the space microgravity and ionizing radiation conditions that significantly influence organisms. Changes in the genomics, physiology, phenotype, growth and metabolites of organisms in real and simulated microgravity and radiation conditions are illustrated. Results of space biological experiments show that the space environment has significant scientific, technological and commercial potential. Combined these potentials can help address the future of life on Earth, part of goal e of astrobiology.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Agricultural plants; evolution; microgravity; radiation; space; space-breeding; stress-induced mutation

Influence of Different Light-Dark Cycles on Motility and Photosynthesis of Euglena gracilis in Closed Bioreactors - Richter, Peter; Strauch, Sebastian; Ntefidou, Maria; Schuster, Martin; Daiker, Viktor; Nasir, Adeel; Haag, Ferdinand; Lebert, Michael (Astrobiology, 2014)
The unicellular photosynthetic freshwater flagellate Euglena gracilis is a promising candidate as an oxygen producer in biological life-support systems. In this study, the capacity of Euglena gracilis to cope with different light regimes was determined. Cultures of Euglena gracilis in closed bioreactors were exposed to different dark-light cycles (40 W/m(2) light intensity on the surface of the 20 L reactor; cool white fluorescent lamps in combination with a 100 W filament bulb): 1 h-1 h, 2 h-2 h, 4 h-4 h, 6 h-6 h, and 8 h-16 h, respectively. Motility and oxygen development in the reactors were measured constantly. It was found that, during exposure to light-dark cycles of 1 h-1 h, 2 h-2 h, 4 h-4 h, and 6 h-6 h, precision of gravitaxis as well as the number of motile cells increased during the dark phase, while velocity increased in the light phase. Oxygen concentration did not yet reach a plateau phase. During dark-light cycles of 8 h-16 h, fast changes of movement behavior in the cells were detected. The cells showed an initial decrease of graviorientation after onset of light and an increase after the start of the dark period. In the course of the light phase, graviorientation increased, while motility and velocity decreased after some hours of illumination. In all light profiles, Euglena gracilis was able to produce sufficient oxygen in the light phase to maintain the oxygen concentration above zero in the subsequent dark phase. Key Words: Euglena gracilis-Bioreactor-Light-dark cycle-Motility-Gravitaxis. Astrobiology 14, 848-858.

Operation of an enclosed aquatic ecosystem in the Shenzhou-8 mission - Li, Xiaoyan; Richter, Peter; Hao, Zongjie; An, Yanjun; Wang, Gaohong; Li, Dunhai; Liu, Yongding; Strauch, Sebastian; Schuster, Martin; Haag, Ferdinand; Lebert, Michael (Acta Astronautica, 2017)
Long- term spaceflight needs reliable Biological life support systems (BLSS) to supply astronauts with enough food, fresh air and recycle wasters, but the knowledge about the operation pattern and controlling strategy is rear. For this purpose, a miniaturized enclosed aquatic ecosystem was developed and flown on the Chinese spaceship Shenzhou-8. The system with a total volume of about 60 mL was separated into two chambers by means of a gas transparent membrane. The lower chamber was inoculated with Euglena gracilis cells, and the upper chamber was cultured with Chlorella cells and three snails. After 17.5 days flight, the samples were analyzed. It was found that all snails in the ground module (GM) were alive, while in the flight module (FM) only one snail survived. The total cell numbers, assimilation of nutrients like nitrogen and phosphorus, soluble proteins and carbohydrate contents showed a decrease in FM than in GM. The correlation analysis showed upper chambers of both FM and GM had the same positive and negative correlation factors, while differential correlation was found in lower chambers. These results suggested primary productivity in the enclosed system decreased in microgravity, accompanied with nutrients assimilation. The FM chamber endured lacking of domination species to sustain the system development and GM chamber endured richness in population abundance. These results implied photosynthesis intensity should be reduced to keep the system healthy. More Chlorella but less Euglena might be a useful strategy to sustain system stability. It is the first systematic analysis of enclosed systems in microgravity.
Keywords: Chlorella pyrenoidosa; enclosed aquatic ecosystem; Euglena gracilis; life support system; microgravity; Shenzhou-8

Restart capability of resting-states of Euglena gracilis after 9 months of dormancy: preparation for autonomous space flight experiments - Strauch, Sebastian; Becker, Ina; Pölloth, Laura; Richter, Peter; Haag, Ferdinand; Hauslage, Jens; Lebert, Michael (International Journal of Astrobiology, 2017)
Dormant states of organisms are easier to store than the living statebecause they tolerate larger variations in  temperature, light, storage space etc., making them attractive for lab culture stocks and also for experiments under special circumstances, especially space flight experiments. Like several other organisms, Euglena gracilis is capable of forming desiccation tolerant resting states in order to survive periods of  unfavorable environmental conditions. In earlier experiments it was found that dormant Euglena cells must not become completely desiccateed. Some residual moisture is required to ensure recovery of the resting states. To analyze the water demand in recovery of Euglena resting states, cells were transferred to a defined amount of cotton wool (0.5 g). Subsequently different volumes of medium (1, 2, 3, 4, 5, 8, 10, and 20 mL) were added in order to supply humidity; a control was set up without additional liquid. Samples were sealed in transparent 50 mL falcon tubes and stored for 9 months under three different conditions: Constant low light conditions in a culture chamber at 20° C, In a black box, illuminated with short LED-light pulses provided by joule thieves, and In darkness in a black box. After nine months, cells were transferred to fresh medium and cell number, photosynthetic efficiency, and movement behavior was monitored over 3 weeks. It was found that cells recovered under all conditions except in the control, where no medium was supplied. Transcription levels of 21 genes were analyzed with a Multiplex-PCR. One hour after rehydration 5 of these genes were found to be up-regulated: ubiquitin, HSP70, HSP90, the calcium-sensor protein frequenin and a distinct protein kinase (PKA), which is involved in gravitaxis. The results indicate a transient general stress response of the cells.
Keywords: dormancy; resting states; Euglena gracilis; recovery; HSP70; HSP90; Multiplex-PCR; ubiquitin; frequenin; PKA